Exploring Factors Influencing Dietary Management in Chinese Chronic Kidney Disease Patients Based on the COM-B Model: A Qualitative Study - Zhang N; Fan S; Wang S; Zhao Y; Liu H; Wei Y; Li Z; Wang W; Liu F (Risk Management and Healthcare Policy)
Na Zhang,1,* Siyu Fan,1,* Shiyu Wang,1 Yu Zhao,1 Hongyuan Liu,1 Yaodi Wei,1 Zhi Li,1 Weiguo Wang,2 Fengping Liu1 1Wuxi School of Medicine, Jiangnan University, Wuxi, People’s Republic of China; 2Department of Urology, Suzhou Hospital, Affiliated Hospital of Medical School, Nanjing University, Suzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Weiguo Wang, Department of Urology, Suzhou Hospital, Affiliated Hospital of Medical School, Nanjing University, Suzhou, 215000, People’s Republic of China, Email shuodanwang@ln.hk Fengping Liu, Wuxi School of Medicine, Jiangnan University, Wuxi, 214122, People’s Republic of China, Email liulaoshiyc@jiangnan.edu.cnBackground: Dietary management plays an important role in slowing the progression of chronic kidney disease, however, adherence to dietary management remains a significant challenge, particularly in culturally diverse settings like China. Currently, there is limited research on the factors influencing dietary management in Chinese patients with chronic kidney disease. Given this knowledge gap, we aimed to explore the factors influencing dietary management in patients with chronic kidney disease based on the capability, opportunity, motivation, and behavior (COM-B) model and provide culturally suitable insights for the creation of focused interventions.Methods: Semi-structured interviews were conducted between September and November 2024 at the Department of Nephrology, Affiliated Central Hospital of Jiangnan University, with 45 participants, including 19 patients with chronic kidney disease, 10 caregivers, and 16 healthcare professionals. Interview guide themes were informed by the COM-B model. Adoption of a thematic analysis approach and mapping onto the COM-B model. The study was reported following the COREQ Checklist.Results: Fifteen factors influencing dietary management in chronic kidney disease were categorized according to the COM-B model’s three domains: (1) Capability: physical dysfunction, difficulty in controlling physiological needs, knowledge mastery, willpower and self-control, low self-efficacy; (2) Opportunity: patient-to-patient influence, social support, social culture, limitations in food and advocacy resources, lack of meals for chronic kidney disease patients in hospital canteens; (3) Motivation: value orientation, dietary expectations, experience-driven (a: perceived benefits, b: perceived burden, c: stigma), nervousness, food desires.Conclusion: This study provides a novel perspective on factors influencing dietary management in chronic kidney disease, highlights the profound impact of Chinese culture on dietary management, and provides a basis for the development of targeted, culturally appropriate intervention programs based on the dimensions of competence, opportunity, and motivation.Keywords: renal insufficiency, chronic, COM-B model, diet therapy, dietary adherence, qualitative research